2023
DOI: 10.1007/s12033-023-00784-1
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Materials for Drug Delivery and Tissue Engineering Applications

Abstract: Nanotechnology and nanostructured materials for drug delivery and tissue engineering applications are relatively new field that is constantly advancing and expanding. The materials used are at the nanoscale level. Recently, great discoveries and applications have been made (Agents for use in chemotherapy, biological agents and immunotherapy agents) in the treatment of diseases in various areas. Tissue engineering is based on the regeneration and repair of damaged organs and tissues by developing biological sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…Apart from mechanical support to the 3D scaffolds Au nanoparticles represent ideal candidates for the delivery of drugs, growth factors and DNA or RNA genes in the cells. This way, the TTE scaffolds mimic the function of ECM and enhance cellular and biological responses [45]. In a recent research, Radwan-Praglowska et al [46] reported the development of 3D biomaterial scaffolds of poly(lactic acid), PLA nanofibers.…”
Section: Tissue Engineering In Cancer Therapeutics: Regenerative Medi...mentioning
confidence: 99%
“…Apart from mechanical support to the 3D scaffolds Au nanoparticles represent ideal candidates for the delivery of drugs, growth factors and DNA or RNA genes in the cells. This way, the TTE scaffolds mimic the function of ECM and enhance cellular and biological responses [45]. In a recent research, Radwan-Praglowska et al [46] reported the development of 3D biomaterial scaffolds of poly(lactic acid), PLA nanofibers.…”
Section: Tissue Engineering In Cancer Therapeutics: Regenerative Medi...mentioning
confidence: 99%
“…One of the primary concerns lies in their lack of biocompatibility and potential toxicity. Engineered materials can trigger immune responses and cause cytotoxicity, limiting their application in biomedical settings [38]. Moreover, synthetic nanoparticles often encounter accumulation issues, which can lead to potential long-term adverse effects [39].…”
Section: Endogenous Evs Advantages Over Synthetic Nanocarriersmentioning
confidence: 99%